PENGARUH PENAMBAHAN SANTAN TERHADAP RENDEMEN DAN TINGKAT KESUKAAN (UJI HEDONIK) KONSUMEN PADA ABON IKAN MANYUNG (Arius thalassinus) - Vita Yanuar; Duwi Febriartin (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
In West Kotawaringin Regency, there is only one home industry that processes catfish as shredded fish. The processing of shredded fish is carried out using only fish meat and spices, without the use of additional ingredients such as coconut milk. This study aims to determine the effect of adding coconut milk to the yield of shredded catfish and the level of consumer preference for shredded catfish. The type of research used is descriptive quantitative. The sampling technique used was random sampling method (random sample) with 30 panelists. The research design used was a single factor Completely Randomized Design (CRD), which became a factor, namely the addition of coconut milk. The data analysis technique used ANOVA (Analysis of Variance) and Tukey's follow-up test used SPSS 16.0. Based on the results of the study, the addition of coconut milk had a significantly different effect on the yield of shredded catfish with a value of Fcount (106.627) > Ftable (3.24). The addition of coconut milk had no effect on the level of consumer preference for the three treatments of shredded catfish (A1, A2 dan A3). The hedonic test value shows that sample A2 (20% coconut milk) has a color (4.17) and a texture (4.20) which is much preferred by consumers